2012
DOI: 10.1159/000341418
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Gastroesophageal Reflux Symptoms in Patients with Non-Alcoholic Fatty Liver Disease Associated with Serum Levels of Triglyceride and Cholesterol but Not Simple Visceral Obesity

Abstract: Background/Aims: Visceral obesity is commonly involved in the pathogenesis of gastroesophageal reflux disease (GERD) and non-alcoholic fatty liver disease (NAFLD). However, other characteristic factors different from visceral obesity are associated with the pathogenesis of NAFLD. We investigated the prevalence of GERD symptoms in patients with NAFLD and its associated risk factors. Methods: NAFLD (n = 96) and controls (n = 139) were enrolled in this study. GERD symptoms were evaluated by using a frequency scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 60 publications
1
19
0
Order By: Relevance
“…However, other studies have also failed to find an association between BMI and GORD [Solhpour et al 2008;Fujikawa et al 2012]. Other studies have found a positive association but found it to be more robust or only positive in women [Zheng et al 2007;Piretta et al 2007;Breckan et al 2009].…”
Section: Obesity and Gordmentioning
confidence: 98%
“…However, other studies have also failed to find an association between BMI and GORD [Solhpour et al 2008;Fujikawa et al 2012]. Other studies have found a positive association but found it to be more robust or only positive in women [Zheng et al 2007;Piretta et al 2007;Breckan et al 2009].…”
Section: Obesity and Gordmentioning
confidence: 98%
“…This finding was consistent with other study in non-alcoholic fatty liver disease population, which described that the severity of GERD was positively correlated with insulin resistance, but not with BMI. 33 Although the obesity proportion based on BMI was equal, there was a prominent difference of waist circumference between groups. Waist circumference is more sensitive than BMI in predicting insulin resistance.…”
Section: Insulin Resistance In Erosive and Non-erosive Reflux Diseasementioning
confidence: 93%
“…At the same time, the rate of H. pylori infection in Japan is on the decrease. Under these circumstances, the prevalence of GERD is expected to increase in Japan, as has been seen in Western countries ( Fujiwara and Arakawa, 2009 ; Fujikawa et al, 2012 ). The reflux of gastric contents, consisting primarily of gastric acid, is reported to be principal source of the pathogenesis of GERD ( Vakil et al, 2006 ).…”
Section: Clinical Efficacies Of Rikkunshito For Upper Gi Symptomsmentioning
confidence: 97%